Peningkatan Hasil Belajar Matematika Menggunakan Media Make A Match Di Sekolah Dasar - Septi Harta Linda; Imam Fitri Rahmadi; Fandi Nugroho (CENDEKIAWAN, 2025)
One of the fundamental materials that students must master is fractions, as it is closely related to everyday life and future applications. In learning fractions, understanding the initial concept is crucial. However, fractions can be challenging for students because they involve numbers divided into two parts separated by a line, yet understood as a single unit. To address this, the researcher used the Make a Match media to enhance students' understanding of the material, which in turn impacted their learning outcomes. This study employed a Classroom Action Research (CAR) method, consisting of two learning cycles. Data and information were collected through observation sheets and test results, which were then analyzed quantitatively. The results showed an increase in students' understanding, as indicated by the average score, which rose from 60,33% to 78.50%. It can be concluded that using Make a Match media makes students learn more actively and enthusiastically, resulting in better learning outcomes.